Innovative Project Clusters in the System of Forming Competitiveness and Economic Development of Regional Art Educational Institutions - Yakushev, O.; Trushkina, N. (Економічний вісник Донбасу, 2023)
The article is devoted to pressing issues of development and implementation of regulatory economic policy in the field of creating innovative educational clusters as a tool for shaping a smart economy. Provided and reasonably generalized vision of regional policy as a complex phenomenon. The conceptual foundations of the formation of the cluster policy of the region are proved and systematically argued, which, unlike the existing ones, is based on the scenario, development of targeted plans and development projects for individual regions, substantiation of the direction of measures to promote the development of clusters, determination of methods, levers and appropriate types of managerial impact, implementation which at the regional level will achieve a socio-economic effect for each participant in cluster interaction. The conceptual vision of the regional policy of clustering is provided on the basis of stimulating the innovative and educational space of the region and the basic principles are determined that should ensure the successful implementation of managerial regulatory influence – the knowledge-intensiveness and the relationship with innovative scientific developments; complexity in analysis, diagnostics of processes, decision making; synergistic combination of knowledge; optimization of costs, time and resources and others. Статтю присвячено актуальним питанням розробки та впровадження регуляторної економічної політики у сфері створення інноваційно-освітніх кластерів як інструменту формування смарт-економіки. Надано та обґрунтовано узагальнене бачення регіональної політики як комплексного явища. Доведено та системно аргументовано концептуальні основи формування кластерної політики регіону, що, на відміну від наявних, базуються на алгоритмі сценарування, розробленні цільових планів та проектів розвитку окремих регіонів, обґрунтуванні спрямованості заходів сприяння розвитку кластерів, визначенні методів, важелів та доцільних видів управлінського впливу, реалізація яких на рівні регіону дозволить досягти соціально-економічного ефекту для кожного учасника кластерної взаємодії. Надано концептуальне бачення регіональної політики кластеризації на основі стимулювання інноваційно-освітнього простору регіону та визначено базові принципи, що повинні забезпечити успішну реалізацію управлінського регуляторного впливу − наукоємність та зв’язок з інноваційними науковими доробками; комплексність в аналізі, діагностуванні процесів, прийнятті рішень; синергетичне поєднання знань; оптимізація витрат, часу та ресурсів та інших.